Ethnic variation of genetic (idiopathic) generalized epilepsy in Malaysia - Lim, K.S.; Ng, C.C.; Chan, C.K.; Foo, W.S.; Low, J.S.Y.; Tan, C.T. (Elsevier, 2017)
Purpose Ethnic variation in epilepsy classification was reported in the Epilepsy Phenome/Genome Project. This study aimed to determine the ethnic variation in the prevalence of genetic (idiopathic) generalized epilepsy (GGE) and GGE with family history in a multi-ethnic Asian population in Malaysia. Method In this cross-sectional study, 392 patients with a clinical diagnosis of GGE were recruited in the neurology outpatient clinic, University of Malaya Medical Centre (UMMC), from January 2011 till April 2016. Results In our epilepsy cohort (n = 2100), 18.7% were diagnosed to have GGE. Of those, 28.6% >(N = 112) had family history of epilepsy with a mean age of seizure onset of 16.5 years old, and 42.0% had myoclonic seizures (N = 47). The lifetime prevalence of epilepsy among first-degree relative of those with GGE and positive family history was 15.0%. Analysis according to ethnicity showed that Malaysian Chinese had the lowest percentage of GGE among those with epilepsy (12.3%), as compared with Indian and Malay (25.3% and 21.3%, p < 0.001). In addition, 32.1% of these Indian patients with GGE had positive family history, which is more than the Malay (26.4%) and Chinese (27.5%) ethnic groups. Consanguineous marriage was noted in 5 Indian families with positive family history (9.6%). Conclusion There was ethnic variation in the prevalence of GGE, whereby the Malaysian Chinese had the lowest percentage of GGE as compared with Indian and Malay. A substantial proportion of GGE had positive family history among the three ethnics groups.